Tantangan dan Peluang dalam Digitalisasi Badan Usaha Milik Desa - Novayanti Sopia Rukmana Syafrin; Nur Fadhila Umar; Sulmiah; Asri Nur Aina; Dyan Paramitha Darmayanti (RUANG KOMUNITAS: Jurnal Pengabdian Masyarakat, 2023)
The current era of digitalization has had a major impact on various sectors. One of them is the Village Owned Business Entity (BUM Desa). The demand for development in the management of BUM Desa includes improving product quality and marketing methods. This training aims to provide participants with an understanding of the challenges and opportunities in digitizing BUM Desa. This training was attended by Bum Desa members who have formed and managed BUM Desa. After attending the BUM Desa challenges and opportunities training, participants are expected to be able to know about how to manage and develop quality BUM Desa products and how to market BUM Desa products and technology-based business management, such as inventory management systems, financial management systems, and sales and marketing management systems, technology-based marketing and promotion. After the training was carried out, the participants already knew about digitization, challenges and opportunities in digitizing BUM Desa.